METACOGNITIVE READING STRATEGIES USED BY ENGLISH-MAJORS AT A UNIVERSITY IN VIETNAM - Ngoc, Dinh Thi Bich; Nhung, Vu Thi (VNU Journal of Foreign Studies, 2022)
Metacognitive reading strategies which include (1) global reading strategies, (2) support reading strategies, (3) problem solving strategies are critical for effective reading comprehension (Mokhtari  & Reichard, 2002). This research aims to explore how high-achieving and low-achieving students at Faculty of Foreign Languages at a university in Vietnam use metacognitive reading strategies in comprehending English reading texts. A mixed research method is employed with two data collection instruments - a survey questionnaire adopted from MARSI Scale by Mokhtari and Reichard (2002) and semi-structured interviews. Forty two English-majors participated in the questionnaire, then representatives of high-achievers and low-achievers participated in semi-structured interviews to provide deeper information. The findings revealed students’ different frequency levels of using metacognitive reading strategy groups in reading comprehension. Additionally, the results indicated how frequently each metacognitive reading strategy is used by the high-achievers and low-achievers. This research would enhance teachers’ awareness of using metacognitive reading strategies for English majors at their different levels and suggest how they instruct their students of different levels to practice metacognitive reading strategies appropriately and effectively.